HUBUNGAN PENEMPATAN KARYAWAN TERHADAP PRESTASI KERJA PADA PT SANDHY PUTRA MAKMUR CABANG JAKARTA - Boma Jonaldy Tanjung; Ahmad Jaenuddin (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
Placement is not a simple matter because the wrong placement will be felt as a result not only on the work unit concerned but also on other units, so that the company's operations will be disrupted not only now but in the future. In the placement of employees should pay attention to the academic achievements of employees so that these employees can complete tasks and work and carry out the authority and responsibilities given by the company. On this basis, the author took the title "The Relationship of Employee Placement to Work Performance at PT Sandhy Putra Makmur Jakarta Branch". The research method that the author uses in this study is a method of collecting data by spreading a list of questions. Instrument test analysis method. The results of the study, namely, the value of the relationship between the variable work placement (X) and employee performance (Y) indicated a correlation value of r = 0.670, which means that it is between the value 0.51 - 0.75, meaning that it has a fairly strong relationship, the nature of the relationship is positive, meaning If the work placement is more precise, the employee's work performance will increase in support of company goals. Keywords: Employee Placement, Work Performance.